Synthesis, Characterization And Modification Of SAPO-34 Zeolite Membrane For Separation Of CO2 From Binary Gas Mixtures - Chew, Thiam Leng (2012)
In the present research, silicoaluminophosphate – thirty four (SAPO-34) zeolite membranes were synthesized on  -alumina disc support using (1) direct insitu crystallization and (2) microwave (MW) heating. MW heating formed thinner SAPO-34 membrane (thickness of ~ 1.6  m) with narrower zeolite crystal size distribution (~ 0.6  m) in much shortened synthesis time of 2 hours at 200 oC compared to direct in-situ crystallization. The SAPO-34 membranes synthesized using MW heating were modified by ion-exchange process with Mg2+, Ca2+, Sr2+ and Ba2+cations. The membranes were characterized using TEM, XRD, SEM, TGA, EDS, FT-IR and nitrogen adsorption-desorption.